Pengaruh Manajemen Aset Terhadap Optimalisasi Pengelolaan Aset Daerah dengan Pengawasan dan Pengendalian Sebagai Variabel Mediasi pada Pemerintah Daerah Provinsi Nusa Tenggara Timur - Arifin Arifin; M.E. Perseveranda; Simon Sia Niha; Heny Manafe; Rere Paulina Bibiana; Stanis Man (Dinasti Review, 2022)
Abstract: This study aims to find out: 1) An overview of the level of asset inventory, legal audit, asset valuation, asset monitoring and control, and optimization of asset management in the Provincial Government of East Nusa Tenggara. 2) the significance of the influence of asset inventory, legal audit, and asset valuation, on asset monitoring and control. 3) the significance of the influence of asset inventory, legal audit, asset valuation, and asset monitoring and control on the optimization of asset management. 4) the significance of the influence of asset monitoring and control in mediating the effect of asset inventory, legal audit, and asset valuation on optimizing asset management in the Regional Government of East Nusa Tenggara Province. The collected data were analyzed using descriptive statistics and inferential statistics by applying Smart PLS. The results of the descriptive statistical analysis show that asset inventory is in the good enough category, a legal audit is in a good category, asset valuation is in the good enough category, asset monitoring and control is in the good enough category, optimization of asset management is in a good category. The results of the inferential statistical analysis show that asset inventory has a significant effect on asset supervision and control legal audit has a significant effect on asset supervision and control, asset valuation asset supervision and control, and Asset Monitoring and Control can Mediate the Effect of Asset Inventory, Legal Audit and Asset Valuation on Optimizing Asset Utilization. Abstrak: Penelitian ini bertujuan untuk mengetahui: 1) Gambaran mengenai tingkat inventarisasi aset, legal audit, penilaian aset, pengawasan dan pengendalian aset, dan optimalisasi pengelolaan aset pada Pemerintah Provinsi Nusa Tenggara Timur. 2) signifikansi pengaruhinventarisasi aset, legal audit, penilaian aset, terhadap pengawasan dan pengendalian aset. 3) signifikansi pengaruh inventarisasi aset, legal audit, penilaian aset dan pengawasan dan pengendalian aset terhadap optimalisasi pengelolaan aset. 4) signifikansi pengaruhpengawasan dan pengendalian aset dalam memediasi pengaruh inventarisasi aset, legal audit, penilaian aset tehadap optimalisasi pengelolaan aset pada Pemerintah Daerah Provinsi Nusa Tenggara Timur. Data yang terkumpul dianalisis menggunakan statistik deskriptif dan statistik inferensial dengan menerapkan Smart PLS. Hasil Analisis statistik Deskriptif menunjukkan bahwainventarisasi aset berada dalam kategori cukup baik, legal audit berada dalam kategori baik, penilaian aset dalam kategori cukup baik, pengawasan dan pengendalian aset kategori cukup baik, optimalisasi pengelolaan aset berada dalam kategori baik. Hasil analisis statistik Inferensial menunjukkan bahwa inventarisasi aset berpengaruh signifikan terhadap pengawasan dan pengendalian asetlegal audit berpengaruh signifikan terhadappengawasan dan pengendalian aset, penilaian aset pengawasan dan pengendalian aset, Pengawasan dan Pengendalian Aset dapat Memediasi Pengaruh Inventarisasi Aset, Legal Audit dan Penilaian Aset terhadap Optimalisasi Pemanfaatan Aset.